HUBUNGAN ANTARA AGAMA DENGAN NEGARA DALAM PEMIKIRAN ISLAM - Mahmud Ishak (IAIN Ambon, 2017)
The study on relationship between religion and state is still debated to the present. The problem begins with the Young Turks revolution under the leadership of Mushthâfa Kemal Pasha, and the peak marked with abolition of the Caliphate and followed by the revocation of Islam as official religion of the state, and abolition of Sharia as the supreme source of law of the state. Finally, Turkey was born as a secular republic that has decisively separated between religious affairs and state affairs. In contrast, other thinkers argue that Islam is most complete religion contained the principles regarding all aspects of life include: ethics, moral, politics, social and economics. Islam is understood not only as a belief, but a complete system and includes a set of answers to the problems experienced by human. It means that there is a relationship between religion and state. This article will analyze the relationship between religion and the state in view of the Islamic thought. Key words: Religion and state relationship, Islamic thought.